An auxin responsive CLE gene regulates shoot apical meristem development in Arabidopsis - Guo, Hongyan; Zhang, Wei; Tian, Hainan; Zheng, Kaijie; Dai, Xuemei; Liu, Shanda; Hu, Qingnan; Wang, Xianling; Liu, Bao; Wang, Shucai (Frontiers in Plant Science, 2015)
Plant hormone auxin regulates most, if not all aspects of plant growth and development, including lateral root formation, organ pattering, apical dominance and tropisms. Peptide hormones are peptides with hormone activities. Some of the functions of peptide hormones in regulating plant growth and development are similar to that of auxin, however, the relationship between auxin and peptide hormones remains largely unknown. Here we report the identification of OsCLE48, a rice (Oryza sativa) CLE (CLAVATA3/ENDOSPERM SURROUNDING REGION) gene, as an auxin response gene, and the functional characterization of OsCLE48 in Arabidopsis and rice. OsCLE48 encodes a CLE peptide hormone that is similar to Arabidopsis CLEs. RT-PCR analysis showed that OsCLE48 was induced by exogenously application of IAA (indole-3-acetic acid), a naturally occurred auxin. Expression of integrated OsCLE48p:GUS reporter gene in transgenic Arabidopsis plants was also induced by exogenously IAA treatment. These results indicate that OsCLE48 is an auxin responsive gene. Histochemical staining showed that GUS activity was detected in all the tissue and organs of the OsCLE48p:GUS transgenic Arabidopsis plants. Expression of OsCLE48 under the control of the 35S promoter in Arabidopsis inhibited shoot apical meristem development. Expression of OsCLE48 under the control of the CLV3 native regulatory elements almost completely complemented clv3-2 mutant phenotypes, suggesting that OsCLE48 is functionally similar to CLV3. On the other hand, expression of OsCLE48 under the control of the 35S promoter in Arabidopsis has little, if any effects on root apical meristem development, and transgenic rice plants overexpressing OsCLE48 are morphologically indistinguishable from wild type plants, suggesting that the functions of some CLE peptides may not be fully conserved in Arabidopsis and rice.